Becoming a Helper, 8th Edition - Marianne Schneider Corey; Gerald Corey (Cengage Learning, 2020)
Ideal for anyone beginning or considering a career in the helping professions, BECOMING A HELPER, Eighth Edition, provides an overview of the stages of the helping process while equipping students with the skills and knowledge to become successful professionals. Drawing on their years of experience, Corey and Corey focus on the struggles, anxieties and uncertainties students often encounter on the road to becoming effective helpers. Emphasizing self-reflection, they provide a candid look at the demands and strains of real-world practice -- helping students decide if this is the right career for them. It is an excellent resource for those planning a career in human services, counseling, social work, psychology, couples and family therapy, or related professions and helpers just starting their careers.